Twenty Years of Change : A Systematic Literature Review of Indonesian Teachers’ Responses to Curriculum Change - Nasution, Innarcaya Nadiar; Indrasari, Stephanie Yuanita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study investigates Indonesian teachers' responses to curriculum changes over the past twenty years, involving four curriculum changes. This study employed a qualitative approach, conducting a systematic literature review conforming to PRISMA 2020 guidelines. Utilizing databases such as Scopus, ERIC, EBSCO, ProQuest, Taylor & Francis, Science Direct, and Google Scholar with selection criteria focused on empirical studies capturing Indonesian teacher's responses toward curriculum changes within the last 20 years (2003-2023). Screening and quality assessment resulted in 26 studies for detailed content analysis. The findings showed teachers’ general openness and acceptance of new curricula, yet this does not translate into effective implementation and reliance on traditional methods. Persistent difficulties include struggles applying student-centered learning, developing learning material, authentic assessment, digital proficiency, and tailored curriculum. These challenges were attributed to inadequate training, resource constraints, student difficulties, cultural factors, and teacher practical competence. This review implied the need to shift schools and local government towards hands-on in-service teacher training and for policymakers to enhance effectiveness through a system of monitoring and incentives. It also suggested a re-evaluation of pre-service training and teacher recruitment criteria, ensuring teachers were equipped for transforming educational practices in Indonesia.